KARAKTERISTIK SITIRAN PADA JURNAL PERPUSTAKAAN PERTANIAN BOGOR - Mafar, Fiqru (Universitas Lancang Kuning, 2010)
This study was carried out to find out citation literature characteristic, wich were published in the